The Results of Learning Management on Thai Manners of Prathomsuksa 2 Students by Using Role Play Learning Management - ใจหงิม, อารีรัตน์ (Education journal Faculty of Education, Nakhon Sawan Rajabhat University, 2022)
The purposes of this research were to 1) compare of Learning achievement on Thai manners of prathomsuksa 2 students before and after studying by role play learning management 2) to study the satisfaction of prathomsuksa 2 students towards role playing learning on Thai etiquette. The samples were 30 prathom Suksa 2/1 students derived from simple randomness. The tools used in this research consisted of 1) plan for learning about Thai manners, 8 hours 2) test of achievement before learning - after learning Thai manners, there are a total of 20 questions and 3) satisfaction assessment form with role - based learning management. The statistics used in data analysis were mean, standard deviation and t-test. The results were as follows: 1) Prathomsuksa 2 students studying with a role play learning management have higher academic achievement after studying statistical significance at the level of .05 and 2) Prathomsuksa 2 students studying with a role play learning management about Thai manners overall, it is in the highest level.